Imaging quantum dot formation in MoS2 nanostructures. (14th August 2018) - Bhandari, S; Wang, K; Watanabe, K; Taniguchi, T; Kim, P; Westervelt, R M
Abstract: Among two-dimensional materials, semiconducting ultrathin sheets of MoS2 are promising for nanoelectronics. We show how a scanning probe microscope (SPM) can be used to image the flow of electrons in a MoS2 Hall bar sample at 4.2 K allowing us to understand device physics at the nanoscale. The SPM tip acts as a movable gate and capacitively couples the SPM tip to the device below. By measuring the change in device conductance as the tip is raster scanned across the sample, spatial maps of the device conductance can be obtained. We present images showing the characteristic 'bullseye' pattern of Coulomb blockade conductance rings around a quantum dot formed in a narrow contact as the carrier density is depleted with a backgate. These images show that multiple dots are created by the disorder potential in MoS2 . From these SPM images, we estimate the size and position of these quantum dots using a capacitive model.